Digitalisation of Public Services in Romania. A Correlational Study - Virlanuta, Florina Oana; Barbuta-Misu, Nicoleta; Bacalum, Silviu; David, Sofia; Moisescu, Florentina (Transformations In Business & Economics, 2024)
The access to digital technologies is fundamentally changing the way that public administration works, transforming the citizen from a passive beneficiary into an active participant, and helping to identify solutions to governance challenges. An important objective of the National Recovery and Resilience Plan is the development of a coherent and integrated digital infrastructure at the level of the public administration in Romania that will provide high-quality digital services to both citizens and companies. The purpose of our research is to identify the factors that influence the process of the public service digitalisation acceleration in Romania and to establish the existing correlations between them. The conceptual model illustrates 6 research hypotheses, highlighting the association/correlation relationships between the proposed independent and dependent variables. The study is based on questionnaire analysis, carried out between September 2022 and December 2022, with 177 responses being validated, which formed the basis of further processing for statistical analysis with the help of the SPSS software, version 23. All 6 hypotheses formulated with the help of the concept model, were statistically validated. The correlational study highlights the factors that influence the digitalisation process of public services in Romania and illustrates a significant correlation between the predictor and the dependent variables.
Keywords: digitalisation; public services; public strategy; Romania